Village Capacity Development (Study of Banjarsari Sub-district, Lebak Regency) - Widjayanti, Arifiani; Wibowo, Eddy Kusponco; Handayani, Heny; Denishwara, Rifat (KnE Social Sciences, 2025)
According to the Village Development Index, in the years between 2015 and 2022, the number of very underdeveloped villages was reduced from 13,453 to 4438. In Lebak Regency, Banten Province, from 340 villages, 103 are underdeveloped, 209 are developing, and 28 villages are classified as developed. This research focused on Banjarsari Sub-district, Lebak Regency, Banten Province. It used qualitative research methods such as preliminary field exploration and brainstorming. Three aspects of village capacity development, namely institutional, management, and human resources, were examined. The results indicated several village enterprises (Bumdes) were not functioning correctly regarding institutions. Regarding management, internet/digitalization facilities have yet to be fully exploited by the community, offices, and business community. Regarding human resources, most villagers’ formal education reaches up to junior high school level. Through this research, it is hoped that the gap between underdeveloped, developing, developed, and independent villages in Kabupaten Lebak can be better understood, and measures can be found to develop the capacity of the village so that it has the competitiveness to become a developing developed and independent village.